Recycling and immobilization of zinc extraction residue in clay-based brick manufacturing - Yaraş, Ali; Sutcu, Mucahit; Erdoğmuş, Ertuğrul; Gençel, Osman; Gençel, Osman; Erdoğmuş, Ertuğrul; Yaraş, Ali (Elsevier, 2021)
This study is related to the evaluation of zinc extraction residue, which is released in large quantities in the zinc metal production process and threatens environmental health, as an alternative raw material in the manufacturing of clay-based bricks. Bricks containing zinc extraction residue (5%-40%) were prepared and sintered at 900 degrees C, 1000 degrees C and 1100 degrees C. Fired brick specimens were characterized in terms of environmental risk, physical and mechanical properties. Sintered bricks at 1100 degrees C exhibited the different behaviors than others due to the vitrification phenomenon. Compared to the sintering temperatures, the compressive strength (39.22 MPa) and bulk density (2.31 g/cm(3)) of samples with 40% ZER at 1100 degrees C were higher than specimens at 900 degrees C and 1000 degrees C, while the porosity (3.1%) and water absorption (1.3%) values were lower. The solubility values of all metals, except for Pb, for all fired bricks with ZER at 900 degrees C, 1000 degrees C and 1100 degrees C are below the limit values according to TCLP standard. However, Pb could only be immobilized (<5 ppm) in ceramic body at 1100 degrees C for all additive rates. Pb release is within acceptable limits up to 10% (3.528 ppm) and 30% (4.989 ppm) ZER addition at 900 degrees C and 1000 degrees C, respectively. Experimental findings demonstrate that reuse of zinc extraction residue in the brick and ceramic manufacturing contributes to the improvement of product properties and immobilization of heavy metals.
Keywords: Brick; Recycling; Vitrification; Leach; Immobilization